Maternal and Fetal outcomes in Premature Rupture of Membranes - Kainaat; Ambreen Naz; Farah Naz; Anum Mumtaz; Rabail Malik; Kubra; Raishem (Indus Journal of Bioscience Research, 2025)
Objective: This study aimed to evaluate the maternal and fetal outcomes associated with term premature rupture of membranes (PROM), with a focus on identifying clinical and laboratory factors that contribute to adverse outcomes. The goal was to determine the impact of PROM-to-delivery interval, infection markers, and delivery mode on neonatal and maternal complications. Methodology: This descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Peoples University of Medical and Health Sciences for Women (PUMHSW), Nawabshah, over six months (November 02, 2023 to May 01, 2024). A total of 50 women with confirmed term PROM were enrolled using non-probability purposive sampling. The Inclusion criteria were singleton pregnancies at ≥37 weeks of gestation with spontaneous rupture of membranes before the onset of labor. Exclusion criteria included multiple gestation, known fetal anomalies, and preterm PROM. Data was collected using a structured proforma and analyzed using SPSS. Descriptive and inferential statistics were used to explore trends and test associations between variables, with p18 hours) was significantly associated with maternal complications, including chorioamnionitis (30%) and postpartum endometritis (48%) (p